#### Answer

$(1-i)^3 = -2-2i$

#### Work Step by Step

$(1-i)^3 = (1-i)^2~(1-i)$
$(1-i)^3 = (1-2i-1)~(1-i)$
$(1-i)^3 = (-2i)~(1-i)$
$(1-i)^3 = -2-2i$

Chegg costs money, GradeSaver solutions are free!

Published by
Pearson

ISBN 10:
978-0-13-421743-7

ISBN 13:
978-0-13421-743-7

$(1-i)^3 = -2-2i$

$(1-i)^3 = (1-i)^2~(1-i)$
$(1-i)^3 = (1-2i-1)~(1-i)$
$(1-i)^3 = (-2i)~(1-i)$
$(1-i)^3 = -2-2i$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.